A review of virtual reality technologies in the field of communication disability: implications for practice and research. (18th May 2020) - Bryant, Lucy; Brunner, Melissa; Hemsley, Bronwyn
Abstract: Background: Technology devices and applications including virtual reality (VR) are increasingly used in healthcare research and practice as tools to promote health and wellbeing. However, there is limited research examining the potential for VR to enable improved communication for people with communication disability. Aims: To review: (a) current research using VR in speech-language pathology; and (b) the ethical and safety considerations of VR research, to inform an agenda for future research applying VR in the field of speech-language pathology. Main contribution: This review reveals that there is an emergent body of literature applying VR to improve or develop physical, psychological and communication interventions. Use of non-immersive virtual environments to provide speech-language pathology assessment or intervention for people with communication disability has demonstrated positive outcomes, with emerging evidence of the transfer of functional communication skills from virtual to real-world environments. However, the use of VR technology and immersive virtual environments in communication disability practice and research introduces safety and ethical issues that must be carefully considered. Conclusions: Research employing VR is in its infancy in the field of speech-language pathology. Early evidence from other healthcare disciplines suggests that VR is an engaging means of delivering immersive and interactive training to build functional skills that can be generalized to the real world. While the introduction of new technology requires careful consideration of research ethics and patient safety, future VR communication research could proceed safely with adequate engagement of interdisciplinary teams and technology specialists. Implications for rehabilitation: Immersive virtual reality may be used in rehabilitation to simulate natural environments to practice and develop communication skills. The sense of immersion that can be achieved using virtual reality may promote the generalization of skills learnt during clinical rehabilitation to real-world situations. Ethical and safety considerations, including cybersecurity and cybersickness, must be carefully monitored during all virtual reality research.